Ambient climatic conditions and semen quality: a comparative analysis across the periods before, during, and after the COVID-19 pandemic - Kim, Heeyon; Park, Soyeong; Kim, Yebon; Chung, Yun Soo; Baek, Jin Kyung; Yoon, Jeongmi; Ryu, Chungsoon; Yun, Bo Hyon; Choi, Young Sik; Pak, Daewoo; Seo, Seok Kyo; Ko, Yohan (Frontiers in Endocrinology, 2025)
IntroductionAmbient temperature and humidity can influence male reproductive function; however, it is unclear whether pandemic-related lifestyle and environmental changes modify this climatic susceptibility.MethodsA total of 2,672 semen analysis records from 1,287 Korean men collected between 2018 and 2024 were analyzed. Data analyses were conducted on a cohort in which some participants underwent multiple semen analyses across different visits. Semen quality data were linked to regional meteorological records for temperature and humidity across two exposure windows: 0–90 days and 70–90 days prior to semen collection. To address intra-subject correlations from repeated measurements, generalized linear mixed-effects models with a Tweedie distribution and log link function were applied. Associations between lagged environmental exposures and semen parameters—including volume, sperm concentration, motility, strict morphology, and total sperm count (TSC)—were evaluated. Subgroup analyses were further performed for the before COVID-19, during COVID-19, and after COVID-19 periods.ResultsSperm concentration and TSC significantly increased during the COVID-19 pandemic, whereas semen volume declined over time. Sperm concentration increased after the COVID-19 period, compared to the before COVID-19 era. Elevated ambient temperature, particularly during the 70–90-day spermatogenesis-sensitive window, was significantly associated with decreased sperm concentration and TSC; however, only during the COVID-19 period. No consistent association between humidity and semen parameters was observed.DiscussionThese results suggest that pandemic-related changes may have amplified biological vulnerability to climatic stressors. Overall, semen quality improved during the COVID-19 pandemic; however, our findings indicate that this period was uniquely characterized by increased climatic sensitivity of spermatogenesis. This may reflect altered environmental exposure and lifestyle behaviors, highlighting the complex interactions between public health crises, human behavior, and male reproductive health. Future studies should incorporate detailed indoor climate and occupational exposure data to elucidate these associations further.